Effect of Prominent Asset Liability Management Risk Components on the Financial performance of Nigerian Commercial Banks - Akinselure, Oluwafemi Philip; Ayoola, Tajudeen John; Aregbesola, Olateju Dolapo; Adenikinju, Olayinka (International Journal of Economics and Financial Issues, 2024)
Asset liability management (ALM) policies of most commercial banks comprise of various risks components, Still only three (i.e. liquidity risk, credit risk and interest rate) are said to be prominent, and, most existing studies relating to ALM of banks, have omitted some of these key risks. The study is on the effect of prominent asset liability management risk components on the financial performance of banks in Nigeria, the study adopted pool regression analysis, mean, etc. The data for the study were obtained from annual reports of the banks in Nigeria, and purposive sampling techniques was used to select them. The findings of the study revealed that, the three prominent asset liability management risk component had a statistically significant impact on financial performance of the banks because all the P-values (i.e.0.0054,0.0179 and 0.0010) of this variables obtained from the pool regression analysis were < 5%. The study concluded that management of commercial banks must ensure that these three prominent ALM risk components are part of their asset liability management policies, since, they have direct effect on the financial performance of the bank.